2008
DOI: 10.1161/hypertensionaha.107.106773
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Carotid Intima-Media Thickness in Grade I Hypertensive Subjects

Abstract: Abstract-We studied 74 never-treated grade I hypertensive subjects aged 18 to 45 years and 20 normotensive control subjects to define the rate of increase in carotid intima-media thickness (IMT) and the potential role played by the various risk factors. IMT was assessed as mean IMT and as maximum IMT in the right and left common carotid artery, carotid bulb, and internal carotid artery at baseline and at the 5-year follow-up. In grade I hypertensive subjects, both mean IMT and mean of maximum IMT were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 31 publications
7
47
1
6
Order By: Relevance
“…There was no significant difference between patients with WCHT and those with SHT (P = 0.27). This increase in IMT was associated with triglyceride levels, age and mean arterial pressure at ABPM, as determined by multivariate regression analysis [37] . In a cross-sectional survey that included 2915 Japanese patients aged ≥ 40 years, the carotid IMT was significantly thicker in WCHT patients than in NT patients (0.73 mm vs 0.67 mm, P = 0.001) [38] .…”
Section: Prognosis and Stroke Risk In Patients With White-coat Hypertmentioning
confidence: 82%
See 1 more Smart Citation
“…There was no significant difference between patients with WCHT and those with SHT (P = 0.27). This increase in IMT was associated with triglyceride levels, age and mean arterial pressure at ABPM, as determined by multivariate regression analysis [37] . In a cross-sectional survey that included 2915 Japanese patients aged ≥ 40 years, the carotid IMT was significantly thicker in WCHT patients than in NT patients (0.73 mm vs 0.67 mm, P = 0.001) [38] .…”
Section: Prognosis and Stroke Risk In Patients With White-coat Hypertmentioning
confidence: 82%
“…In contrast, the HARVEST study by Puato et al [37] compared the baseline and follow-up IMT values in 35 WCHT, 20 NT and 39 SHT patients over five years. The baseline (P = 0.004) and follow-up (P < 0.01) IMT values were significantly higher and increased faster in WCHT patients than in NT controls.…”
Section: Prognosis and Stroke Risk In Patients With White-coat Hypertmentioning
confidence: 99%
“…The hypertensive state is related to progression to more advanced atherosclerosis [30]- [32], calcification of atherosclerosis [32]- [34]. Previous studies using carotid ultrasonography have reported conflicting results with regard to significant differences in IMT of the right and left side: some studies reported a significant difference [16] This study demonstrated the ORs of |ΔSBP| ≥10 mm Hg for the separate and combined effects of obesity and abnormal ABI, regardless of sex and age ( Table 2).…”
Section: Association Of |δSbp| ≥10 MM Hg With Development Of Abnormalmentioning
confidence: 65%
“…Fakat BÖH ile hipertansif hastaların karotis intima media kalınlıkları başlangıçta ve beş yılın sonunda karşılaş-tırıldığında bir fark olmadığı görülmüştür. 14 …”
Section: Beyaz öNlük Hi̇pertansi̇yonu Ve Uç Organ Hasariunclassified